Enterovirus inhibitory activity of C-8-tert-butyl substituted 4-aryl-6, 7, 8, 9-tetrahydrobenzo[4, 5]thieno[3, 2-e][1, 2, 4]triazolo[4, 3-a]pyrimidin-5(4H)-ones. Issue 15 (1st August 2017) - Kumar Biswas, Bishyajit; Malpani, Yashwardhan R.; Ha, Neul; Kwon, Do-Hyun; Soo Shin, Jin; Kim, Hae-Soo; Kim, Chonsaeng; Bong Han, Soo; Lee, Chong-Kyo; Jung, Young-Sik
Graphical abstract: Abstract: Members of a series of 4-aryl-6, 7, 8, 9-tetrahydrobenzo[4, 5]thieno[3, 2- e ][1, 2, 4]triazolo[4, 3- a ]pyrimidin-5(4 H )-ones (1, Fig. 2) were prepared and tested against representative enteroviruses including Human Coxsackievirus B1 (Cox B1), Human Coxsackievirus B3 (Cox B3), human Poliovirus 3 (PV3), human Rhinovirus 14 (HRV14), human Rhinovirus 21 (HRV 21) and human Rhinovirus 71 (HRV 71). The C-8- tert -butyl group on the tetrahydrobenzene ring in these substances was found to be crucial for their enterovirus activity. One member of this group, 1e, showed single digit micromolar activities (1.6–8.85 μM) against a spectrum of viruses screened, and the highest selectivity index (SI) values for Cox B1 (>11.2), for Cox B3 (>11.5), and for PV3 (>51.2), respectively. In contrast, 1p, was the most active analog against the selected HRVs (1.8–2.6 μM), and showed the highest selectivity indices among the group of compounds tested. The SI values for1p were 11.5 for HRV14, 8.4 for HRV21, and 12.1 for HRV71, respectively.